Nonresponse Bias in Survey Estimates of Alcohol Consumption and Its Association With Harm - Dawson, Deborah A (Rutgers University, 2014)
OBJECTIVE: Selective nonresponse represents a major source of potential bias in survey-based estimates of alcohol consumption and its association with harm. This study examined whether consumption differs for respondents and nonrespondents after correcting for their sociodemographic differences. METHOD: This study compared baseline consumption among initial respondents who did (n = 34,653) and did not (n = 5,306) respond to a 3-year follow-up interview in a prospective study of the U.S. general population. Differences in consumption measures were presented before and after adjustment or sociodemographic differences, and interactions of nonresponse with consumption were assessed in models predicting various types of harm. RESULTS: After we adjusted for sociodemographic differences and factored in the overall level of nonresponse (13.3%), the degree to which the prevalence of drinking was underestimated in the total population was only 1.6%, and the extent to which consumption was overestimated among drinkers lay in the range of 1.7% to 2.4%. There was no consistent evidence that nonresponse moderated the association between consumption and alcohol-related harm. Sociodemographic differentials in nonresponse generally matched those reported for cross-sectional studies in the literature. CONCLUSIONS: The extent of nonresponse bias in survey estimates of alcohol consumption should not affect drinking guidelines and planning for prevention and treatment programs. The findings of this study are supportive of study designs that have been used to assess nonresponse bias, including the use of registry data on alcohol-related harms and secondary nonresponse data from prospective studies.